In Vitro and In Vivo Evaluation of Sorghum (Sorghum bicolor L. Moench) Genotypes for Pre- and Post-attachment Resistance against Witchweed (Striga asiatica L. Kuntze) - V. O. Gwatidzo; J. T. Rugare; S. Mabasa; R. Mandumbu; J. Chipomho; S. Chikuta (International Journal of Agronomy)
Sorghum (Sorghum bicolor L. Moench) production in sub-Saharan Africa is seriously constrained by both biotic and abiotic stresses. Among the biotic stresses is witchweed (Striga spp.), a noxious parasitic weed causing major damage in cereal crops, such as sorghum. However, resistance through reduced germination stimulant production or altered germination stimulant composition provides a sustainable and most effective way for managing the parasitic weeds. Laboratory and glasshouse experiments were conducted using seven (7) sorghum genotypes to evaluate their resistance or tolerance the witch weed (Striga asiatica L. Kuntze). The first experiment was a laboratory agar gel assay arranged in a completely randomized design with six (6) replications to evaluate the effects of the seven (7) sorghum genotypes on the production of strigolactones by determining the percentage germination and the furthest germination distance of the Striga seeds. The second experiment was a seven (7) (sorghum genotypes)∗two (2) (Striga treatments) factorial glasshouse experiment conducted to evaluate the effects of Striga on sorghum growth, physiological and yield components of sorghum, Striga syndrome rating, and number of Striga per plant. The genotypes showed a significant (p<0.05) difference in germination percentage and furthest germination of Striga seeds in the agar gel assay. Genotypes SV4, Mahube, and ICSV 111 IN showed the least germination percentage and lowest germination distance, implying that these varieties either produced low strigolactones or altered their composition. In contrast, Kuyuma, Wahi, SV2, and Macia caused high Striga seed germinations and high furthest germination distances, suggesting that these sorghum genotypes were susceptible to Striga infection. The sorghum × Striga × time interactions were significant (p<0.05) on sorghum height. It was found that the heights of sorghum genotypes ICSV 111 IN and Mahube were not altered by Striga infection, but the heights of Kuyuma, Macia, SV2, SV4, and Wahi were reduced by Striga infection. The interaction of sorghum∗Striga effects was significant (p<0.05) on chlorophyll fluorescence. Striga infection did not alter the chlorophyll content of ICSV 111 IN and SV4. The sorghum∗Striga interaction effects were significant (p<0.05) on head index, leaf biomass, leaf index, root biomass, root index, plant biomass, and root : shoot ratio. Assessing Striga tolerance based on sorghum heights, chlorophyll content, and root : shoot ratio parameters, it could be concluded that the sorghum genotypes Mahube, ICSV 111 IN, and SV4 tolerated Striga infection, whereas Kuyuma and SV2 could be susceptible.